Effects of anti-Leishmania compounds in the behavior of the sand fly vector Lutzomyia longipalpis - Ferreira, Tainá Neves (2022)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Bioquímica e Fisiologia de Insetos. Rio de Janeiro, RJ, Brasil.